TECHNOLOGY AND COOPERATIVE ACCOUNTABILITY: APPROACHES TO ORGANIZATIONAL AND MANAGEMENT, BUSINESS AND SERVICES, AND FINANCIAL ASPECTS - Rizki, Novia; Priyambodo, Victoria K; Hanani, Tri; Gayatri, Baiq Alon P. (Universitas Tidar, 2024)
The development of information technology is very rapid in its use, including in the financial reporting sector. This study aims to analyze whether the use of technology has an impact on the accountability of cooperatives in East Lombok. This quantitative study uses a questionnaire with a total of 52 cooperative respondents. Data analysis uses path analysis with the Partial Least Square-Structural Equation Model (PLS-SEM). The results show that the use of technology has a significant effect on the cooperatives’ accountability which is measured comprehensively with three approaches, namely organizational and management, business and service, and financial aspects. This study contributes to the literature on the determinants of cooperative accountability in Indonesia which are very closely related to the use of information technology. In addition, this study provides empirical evidence of the impact of technology use on accountability which is not only measured from a financial aspect.